Some progressive steps in coconut research and development in Sri Lanka through utilization of molecular markers - Perera, Lalith (Journal of Plantation Crops, 2014)
Coconut is the sole species of genus Cocos and as such breeding of coconut is limited to the intra-specific level. Furthermore, the long life cycle, massive stature, highly heterozygous nature, lack of vegetative propagation method, limited number of seeds produced per year and bulkiness of seeds, limit the use of many traditional breeding methods employed in other crops in coconut breeding. Obtaining pure line from heterozygous coconut remained unrealistic because of the long vegetative phase. Thus coconut breeding is confined to mass selection of phenotypically superior parent palms, and to inter and intra-varietal hybridization. All these constraints in coconut breeding make the use of molecular breeding techniques highly attractive. Although identifying molecular markers linked to useful traits and characters to strengthen and fasten the selection and breeding of coconut looks the main goal of using markers, they can be efficiently used for many other applications. This article deals with some other useful applications of molecular markers practically used in the coconut breeding programme in Sri Lanka.